The Santhal: Socio-Economic Miserable Condition and Quality of Life (An Overview of Bantali Rakhasahi Village, Mayurbhanj District, Odisha) - PATEL, SMROOTI PRAJNA; Maharana, Rajeswar (IJRDO - Journal of Social Science and Humanities Research, 2018)
Socio-economic condition signifies an economic and social combined total measure of a person’s work experience and of an individual’s or family’s economic and social position in relation to others; based on income, education and occupation. The tribal population is identified as the aboriginal inhabitants of our country. The Santhal are the third largest tribal communities of India after the Gond and the Bhill with a population over 4.26 million. They are largely distributed in the district of Balasore, Keonjhar, Mayurbhanj and Sundergarh of the state of Odisha. Over fifty percent of the tribal population of the Mayurbhanj district is constituted by the Santhal. The present study makes an attempt to focus on the socio-economic condition of Santhal people of Bantali Rakhasahi village of Mayurbhanj district of Odisha and is an attempt to find out the factors those affect their Socio-Economic conditions. Data have been collected by using different qualitative methods like participant observation, group discussions, interview Scheduled. Sample subjects were drawn randomly from 131Santhal households of the village. Olchiki is their mother tongue. Art, music and dance are highly prized in their culture. Their settled life has made them agricultural community as agriculture is their primary occupation. Their life is intimately connected with the forest and their economy. The community people live more or less in isolation with a very simple lifestyle. They face many problems relating to their day to day life as they are not getting healthy housing facility, proper sanitation facility, proper nutrition, safe drinking water, and other household amenities and so on. For improving their socio-economic conditions some of the basic services should adequately be provided. They need opportunities to develop their socio-economic status. There is a need to put more attention on educational aspects of scheduled tribes, where this only can motivate them for future life. The planners and policymakers have to evolve suitable strategies and formulate relevant policies to enhance tribal development.